Automatic detection of optic disc in color fundus retinal images using circle operator. (August 2018) - Reza, M. Nahid
Highlights: A method is proposed to detect optic disk automatically. No background mask and blood vessel segmentation are required. An operator is designed and applied on fundus retinal images from six databases. Promising results are outcome with high accuracy and low processing time. Abstract: In the field of computer aided eye disease diagnosis, automatic optic disk detection is required. In this paper a method is proposed to detect optic disk automatically in color retinal fundus image without using background mask and blood vessels. Based on the properties of optic disk, an idea of circle operator is presented here. This method has been applied on six public databases and the promising results are obtained. The experimental results indicate that this proposed method of automatic optic disk detection has good accuracy and is also time efficient.